Analisis Kebutuhan dalam Pengembangan Kepemimpinan Transformasional Kepala Sekolah untuk Meningkatkan Karakter Religius Siswa di Sekolah Menengah Pertama - Muhajirin, Ahmad; Hartinah, Sitti; Nafiati, Dewi Amaliah (Universitas Nusantara PGRI Kediri, 2025)
This study aims to design a transformational leadership model for principals that can strengthen students' religious character at the Junior High School (SMP) level. Using a Research and Development (R&D) approach, this study analyzes the need to improve the leadership skills of principals in educating students' religious character. The subjects of the study consisted of five principals and ten teachers from junior high schools in Pemalang Regency, selected using a purposive sampling method. Data collection techniques were carried out through interviews, observations, and questionnaires to identify the challenges faced by principals in implementing transformational leadership. It is hoped that the results of this study will provide recommendations that can improve the effectiveness of leadership based on strengthening students' religious character. The findings of the study revealed that the biggest challenges faced were the lack of training that focused on religious values ​​and the need for a more structured and practical leadership model.